Experimental investigation of the shear behavior at the pervious concrete-sand interface under monotonic loading - Mu’ath I. Abu Qamar; Ammar A. Alshannaq; Mohammad F. Tamimi; Motasem I. Al-Qura’an; Ghayda’a M. Alawneh (Scientific Reports)
Abstract Interaction between soil and structural materials plays a critical role in the overall stability of geotechnical systems such as piles, retaining walls, soil nails, and soil anchors. Pervious concrete is increasingly being used as an alternative for conventional concrete in applications such as evaporative or wet cooling, ground improvement using microbial-induced carbonate precipitation (MICP) biogrouting, or possibly geothermal foundations (energy piles). The motivation and the aim of the present experimental study is to improve the understanding of shear behavior at the interface between pervious concrete and cohesionless soil under mechanical loading. This paper presents results from a series of interface direct shear tests performed on smooth, conventional concrete, pervious concrete of variable surface roughness sheared against fine and medium sands. It was found that the surface roughness of tested surfaces has a remarkable influence on the shear strength and volume change responses at sand-concrete interfaces. In the sand-pervious concrete tests, the interface shear strength and soil dilation increase as the surface roughness increases, which was significantly influenced by the porosity of concrete specimens. The smooth (untextured) interface exhibited a soil contractive behavior and yielded lower interface shear resistance among all surfaces, which is considered as the lower bound of strength. The results presented show that pervious concrete mobilizes interface shear strength and volume change increases with specimen porosity (i.e., 15% vs. 30%) and confining (normal) stress, which yielded a value ranges between 2.82 and 3.46 times of sand-smooth (untextured) surface strength in medium and fine sands, respectively.